Effect of Moringa (Moringa oleifera) leaves on increasing hemoglobin level of female adolescents - Fitria Yulastini; SN Nurul Makiyah; Retno Mawarti (Alma Ata University Press, 2023)
ABSTRACTBackground: Iron deficiency anemia is a dominant cause of anemia in the world, and it is one of the major nutritional problems in Indonesia with high prevalence in female adolescents, which reached 22.7%. Moringa plant (Moringa oleifera) contains rich amount of protein, amino acid, mineral, and vitamin.The use of moringa leaves as an herbal treatment has been developed, with one of its main objectives is to increase the hemoglobin level.Objective: To analyze the effect of moringa (Moringa oleifera) leaves capsule on the hemoglobin level of female adolescents.Method: This was a true experimental study with randomized controlled trial design and simple random sampling. Research samples were 61 anemic female adolescents that were classified into two groups. 31 girls were selected as treatment group where they consumed moringa leaves capsules, and the other 30 girls received iron supplements in control group. The intervention was done twice per day for 21 days. Data of hemoglobin level was analyzed using independent t-test.Results: Hemoglobin level in treatment group before the intervention was 10.75±0.94 gr/dl and it increased to 12.58±0.99 (p-value= 0.000) after the intervention. The level of the control group also increased after intervention with the p-valueof 0.000. The mean hemoglobin level increase in treatment and control groups were 1.82 gr/dland 1.40 gr/dl, respectively. There was a significant difference between hemoglobin level increase between both groups with the p-valueof 0.039(<0.05).Conclusion: The hemoglobin level of female adolescents who consumed moringa (Moringa oleifera) leaves capsules was higher than the ones who only took iron supplements. Keywords : Moringa leaves (Moringa oleifera); iron supplement; hemoglobin level; female adolescent